2005
DOI: 10.1128/jcm.43.5.2303-2306.2005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Vancomycin-Resistant Enterococcus faecium Isolates from Korea

Abstract: A total of 98 vancomycin-resistant Enterococcus faecium (VREF) isolates from four tertiary-care hospitals in Korea during the period between 1998 and 2004 were analyzed for genotypic characteristics using the multiplex PCR, multilocus sequence typing (MLST), pulsed-field gel electrophoresis (PFGE), and esp gene analysis. Ninety-two isolates of VREF with VanA phenotype and five of six isolates with VanB phenotype possessed the vanA gene. MLST analysis revealed 9 sequence types (STs), which belonged to a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
6

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 21 publications
3
54
1
6
Order By: Relevance
“…Several studies performed during outbreaks in Taiwanese hospitals revealed a preferred prevalence of (hospital-associated) vanA-type vancomycinresistant E. faecium strains (Hsieh et al, 2009;Hsieh et al, 2010). In South-Korean hospitals (and outside hospitals) vanA-genotype (VanB phenotype) E. faecium were widely prevalent (Ko et al, 2005;Shin et al, 2006;Park et al, 2008). Recent reports from China revealed also a preferred prevalence of vanA-type vancomycin resistance among clinical VRE (Zheng et al, 2007a;Zheng et al, 2007b;Zhu et al, 2009).…”
Section: Asia Australia and New Zealandmentioning
confidence: 99%
“…Several studies performed during outbreaks in Taiwanese hospitals revealed a preferred prevalence of (hospital-associated) vanA-type vancomycinresistant E. faecium strains (Hsieh et al, 2009;Hsieh et al, 2010). In South-Korean hospitals (and outside hospitals) vanA-genotype (VanB phenotype) E. faecium were widely prevalent (Ko et al, 2005;Shin et al, 2006;Park et al, 2008). Recent reports from China revealed also a preferred prevalence of vanA-type vancomycin resistance among clinical VRE (Zheng et al, 2007a;Zheng et al, 2007b;Zhu et al, 2009).…”
Section: Asia Australia and New Zealandmentioning
confidence: 99%
“…The presence of the esp and hyl gene in isolates was determined by PCR using primers; esp-F (5'-GGTCACAAAGC-CCAACTTGT-3') and esp-R (5'-ACGTCGAAAGTTCGATT-TCC-3') [6] and hyl-F (5'-ACAGAAGAGCTGCAGGAAATG-3') and hyl-R (5'-GACTGACGTCCAAGTTTCCAA-3') [11]. To determine repeat number variations of esp A and C repeats, two different primer combinations were used; espfs7F (5'-CGACCGATTTAGCAGTAAC-3') -espfm5R (5'-CAGCTGC-GCTAACATCTAC-3') and espfm5F (5'-AAAGAAGATTTA-CCAAAAGATACTAAG-3') -espfs3R (5'-TTCGGCGCTTTT-TATC-3') respectively [12].…”
Section: Detection Of the Esp And Hyl Genesmentioning
confidence: 99%
“…The characteristics of CC17 are its resistance to ampicillin and quinolone, and variant esp gene as E. faecium pathogenicity island (PAI) [4,5]. It has been reported that the organisms isolated in Korea belong to CC17 [6,7]. Thus study on epidemiology and genetic characteristics of CC17 is needed.…”
Section: Introductionmentioning
confidence: 99%
“…우리나라에서 분리된 VREF의 대부분은 IS1542와 IS1216V가 삽입되어 있어 유럽에 서 분리된 균주와 매우 유사하며 (Woodford et al, 1998;da Costa Darini et al, 1999) VRE 분리균주 6주에서 7개의 housekeeping 유전자의 염기 서열로 http://efaecium.mlst.net에서 ST를 확인하였을 때 분리균주 Km37, Km39 및 Km40은 ST78로, 분리균주 Km20, Km36 및 Km38은 각각 ST18, ST230 및 ST192로 나타났다 (Table 4). ST18, ST78 및 ST192는 국내 병원에서 분리된 바 있으며, 특히 ST78은 국내에서 가장 흔하게 분리되는 ST이다 (Ko et al, 2005;Lee et al, 2006). ST230은 대한민국 전북의 한 병원에서 분리되 어 MLST database에 등록되어 있다(MLST database ID : 587).…”
Section: 교차접합시험에 의한 내성 유전자의 전이 확인unclassified
“…본 연구에서 확인된 ST를 대상으로 eBURST program을 통 해 MLST database의 410개의 ST와 비교하여 clonal complex (CC)를 확인한 결과를 (Willems et al, 2005;Top et al, 2008), 국내 병원에서 분리되고 있는 대부분의 균주 역시 CC 17에 속한다 (Ko et al, 2005;Lee et al, 2006;Lopez et al, 2009). …”
Section: Tn1546의 구조 분석unclassified